Catheter Based Valve and Aortic Surgery - Ailawadi, Gorav; Kron, Irving L. (Springer New York : Imprint: Springer, 2016)
This text provides a comprehensive, state-of-the-art review of catheter based approaches to valve and aortic diseases.  The scope encompasses involve all the current and upcoming transcatheter aortic valve technologies as well as mitral, pulmonary and tricuspid valve technologies. Aortic diseases including transcatheter repair of descending aneurysms are included and the upcoming technologies designed to repair aortic dissections, traumatic injury, and ascending arch stent repair are highlighted. Catheter Based Valve and Aortic Surgery will be a useful tool for cardiac and vascular surgeons, interventional cardiologists, general cardiologists, and clinicians and researchers with an interest in these exciting new developments in structural heart and vascular diseases.